The role of China’s Investment in Shaping the Redevelopment of Afghanistan - Muhammad Al Amin; Mujibur Rahman Ahmadi; Haidan Angga Kusumah (Rechtsnormen: Journal of Law, 2024)
Background. The Afghanistan-China strategic relationship is multifaceted, characterized by economic convergences, security cooperation, and mutual diplomatic support. China's Belt and Road Initiative has played a significant role in deepening ties, especially through infrastructure development in Afghanistan. Purpose. In this paper authors tried to explore Afghanistan and China relations, how China plays an important role in the redevelopment of Afghanistan, discuss the prospects and challenges facing Chinese–Afghan relations, including from a regional perspective and also discussed how China fits into the vacuum left by the US withdrawal. Method. The method used applies a qualitative method that focuses on looking at social phenomena that occur in society. Results. At the same time, a rather stable Afghanistan free from threats by militant and terrorist groups could provide opportunities for China and other regional states to contribute to its post-conflict economic reconstruction and development. Conclusion. At the period since the Taliban took over an Afghanistan emptied of its foreign presence, there has been much more speculation that China will step in to fill the geopolitical, security and economic vacuum left by the West’s withdrawal. China surely has direct interests in a stable, developed and well-governed Afghanistan, not least to prevent spillover and assets in the wider regions of Central and South Asia.